Perceptions and reflections of embryo donation recipients: a qualitative follow-up study - Seungho Lee; Salomeh Salari; Mona El-Gayar; Joshua Mangels; Rebecca Flyckt; Jody Madeira; Susan Klock; Steven R Lindheim (Gynecology and Obstetrics Clinical Medicine)
Objective Cross-sectional quantitative data from donor embryo recipients suggest children conceived through embryo donation are psychosocially well adjusted with healthy parent–child relationships. This study delves deeper into this topic using a qualitative grounded theory approach to capture recipients’ experiences and perceptions regarding family-building through embryo donation.Methods This was a national qualitative study conducted via semistructured phone interviews. Interviews were self-nominated and composed of 25 open-ended questions. Interviews were transcribed using Temi software and coding was conducted in accordance with grounded theory methodology by five independent researchers to identify themes.Participants came from three embryo donation programmes across the USA. 28 participants, with an average age of 48 years (range: 34–69), volunteered to participate in interviews from a larger subject group. This previous group was a cross-sectional, survey-based study of psychosocial outcomes of children born via embryo donation. The majority of patients (92%) identified as Christian/Catholic.Themes were identified in participants’ responses to questions regarding general perceptions of embryo donation, decision-making process, disclosure and children’s psychosocial adjustment.Results Of the 118 participants from the quantitative survey-based study who volunteered for this qualitative study, 28 individuals (24%) participated in the phone interview before thematic saturation was reached. The main themes identified include a desire to use existing embryos efficiently; religious frameworks encouraging maximal embryo use; satisfaction with and enthusiasm for embryo donation; lack of concern regarding child social adjustment and willingness to disclose donor embryo use to others.Conclusion This qualitative study’s findings affirm that participants find conceiving a child through embryo donation highly satisfying and rewarding, experiencing minimal adverse events or regrets. As respondents identified largely as Christian/Catholic, further studies are warranted to assess the perceptions of a more diverse and generalisable population of recipients and children born via embryo donation.